Incorrect voting in the 2012 U.S. presidential election: How partisan and economic cues fail to help low-information voters. (March 2015) - Dusso, Aaron
Abstract: The importance of voting in undisputed, yet scholarly works attempting to understand the causes and consequences of incorrect voting are relatively scarce. Building on the works of Lau and Redlawsk (1997, 2006; Lau et al., 2008), I design and implement a new survey method measuring incorrect voting I call Self-identified Incorrect Voting (SIV). This method allows survey respondents to determine for themselves if they voted incorrectly in the 2012 U.S. presidential election. I conducted the SIV survey of a national sample of voters and use the results to test traditional hypotheses regarding the value of partisanship and the economy as cues to help low-information voters behave in the same manner as high-information voters. Highlights: New survey measure of incorrect voting called Self-identified Incorrect Voting. Measure allows respondents to determine for themselves if they voted incorrectly. Find that nearly 22 percent of voters indicate that they did so incorrectly in 2012. Test value of partisanship as a cue, find it leads low-information voters astray. Test value of the economy as a cute, find it leads low-information votes astray.